Performance analysis of BDS B1C/B2a PPP using different models and MGEX products. Issue 389 (4th March 2023) - Sun, Mengfei; Liu, Li; Yan, Wei; Liu, Jian; Liu, Tong; Xu, Guochang
Abstract : To assess the precise point positioning performance of the new BDS signals, the observation data of 56 MGEX stations for 30 consecutive days were used to carry out dual-frequency PPP experiments. The positioning results showed that the best positioning performance could be achieved with CODE precise products, followed by IAC, GFZ, and WHU products, with SHA products performing the worst. For Ionosphere-free and undifferenced and uncombined models, the performance of the two was comparable. In addition, our study indicated that station location and time were not the main factors affecting the performance of BDS-3 PPP.